Osteoporosis Risk and Body Mass Index Comparison among Urban and Rural Menopausal Women - Vita Muniarti Tarawan; Putri Fatima Adnantami; Putra Habibie Adnantama; Putra Haqiqie Adnantama (International Journal of Integrated Health Sciences, 2015)
Objective: To compare osteoporosis risk factors between urban and rural menopausal women. Methods: This study applied the causal-comparative analysis to compare osteoporosis risk factors between urban and rural menopausal women. The subjects included in this study were 40 urban and 40 rural menopausal women who were randomly recruited. The respondents’ bone mass density was measured using densitometry. This study also examined several aspects, including the respondents’ nutritional status (body mass index calculation) and physical fitness (VO2 max). The correlation between osteoporosis risk and either nutritional status or physical fitness among urban and rural menopausal women were tested using Chi square correlation analysis. Results: This study examined several aspects, including age (years) 58.7±6.1 (urban) and 58.3±6.5 (rural), p=0.815, body mass index (kg/m2) 23.7±3.7 (urban) and 22.7±3.6 (rural), p=0.221, VO2 max (average) 27 (67.5%) (urban) and 25 (62.5%) (rural), p=0.624. The respondents diagnosed as suffering from osteoporosis were statistically measured for the: nutritional status (body mass index) (under) urban 0%, rural (p=0.789) 2.5%, body mass index 7.5% urban, rural (p=0.571) 2.5%, physical fitness condition (VO2 max) (average) urban 7.5%, rural (p=0.850) 5%, VO2 max (poor) urban 7.5%, rural (p=0.880) 5%. Body mass index and bone mass density calculation results described that the nutritional status of urban and rural menopausal women: normal 12 (30%) vs (32.5%), osteopenia 8 (20%) vs (15%), osteoporosis 3 (7.5%) vs (2.5), p=0.571. Conclusions: This study shows that there is no significant difference between osteoporosis risk and nutritional status and physical fitness in urban and rural menopausal women.Keywords: Nutritional status, osteoporosis level, physical fitness DOI: 10.15850/ijihs.v3n1.402